Two novel dual GLP-1/GIP receptor agonists are neuroprotective in the MPTP mouse model of Parkinson's disease. (1st May 2018) - Feng, Peng; Zhang, Xiangjian; Li, Dongfang; Ji, Chenhui; Yuan, Ziyue; Wang, Ruifang; Xue, Guofang; Li, Guanglai; Hölscher, Christian
Abstract: Type 2 diabetes mellitus (T2DM) is a risk factors for developing Parkinson's disease (PD). Insulin desensitization is observed in the brains of PD patients, which may be an underlying mechanism that promotes neurodegeneration. Incretin hormones are growth factors that can re-sensitize insulin signalling. We have previously shown that analogues of the incretins GLP-1 or GIP have neuroprotective effects in the MPTP mouse model of PD. Novel dual GLP-1/GIP receptor agonists have been developed as treatments for T2DM. We have tested 3 novel dual receptor agonists DA-JC1, DA-JC4 and DA-CH5 in comparison with the GLP-1 analogue liraglutide (all drugs at 25 nmol/kg ip once-daily for 6 days) in the MPTP mouse model of PD (4 × 25 mg/kg ip). In the Rotarod and grip strength assessment, DA-CH5 performed best in reversing the MPTP–induced motor impairment. Dopamine synthesis as indicated by levels of tyrosine hydroxylase was much reduced by MPTP in the substantia nigra and striatum, and DA-CH5 was the best drug to reverse this. Pro-inflammatory cytokines were best reduced by DA-CH5, while expression levels of the neuroprotective growth factor Glial-Derived Neurotrophic Factor (GDNF) was most increased by DA-JC4. Synapses were protected best by DA-JC4 and DA-CH5. Both DA-JC1 and liraglutide showed inferior effects. These results show that a combination of GLP-1 and GIP receptor activation is more efficient compared to single GLP-1 receptor activation. We conclude that dual agonists are a promising novel treatment for PD. The GLP-1 mimetic exendin-4 has previously shown disease modifying effects in two clinical trials in Parkinson patients. Highlights: GLP-1 receptor agonists have shown neuroprotective effects in Parkinson's patients. Two novel GLP-1/GIP receptor agonists show good effects in the MPTP mouse model of PD. Motor activity and dopamine synthesis is restored by both dual agonists. The chronic inflammation response in the brain is much reduced. The expression of the key growth factor GDNF is restored.